Value chains and system dynamics modeling training program - Dizyee, Kanar; Rich, Karl M. (International Livestock Research Institute, 2021)
The value chain training program consist of three modules. Module 1 is focused on traditional qualitative value chain assessment, module 2 is focused on system dynamics (SD) modelling approach and participatory Group Model Building (GMB), and module 3 is about application and getting participants used to how to use SD model and our value chain tools. The first two modules can be delivered independently and together depending on the depth and the purpose of training. The third module is focused on application and using and constructing value chain model using system dynamics approach, it is preferred that the first two modules (or at minimum the second module) is completed before progressing to module 3. Module three can be done in class or participants can follow the link to the manual.